Multivariate assessment of atmospheric deposition studies in Bulgaria based on moss biomonitors: trends between the 2005/2006 and 2015/2016 surveys - Hristozova, Gergana; Marinova, Savka; Motyka, Oldřich; Svozilík, Vladislav; Zinicovscaia, Inga (Environmental science and pollution research international, 2020)
This study aims to investigate the changes in atmospheric deposition trends in Bulgaria, studied using the moss biomonitoring technique since 1995. For the first time, a paired (site-wise) comparison was performed after a critical review of the sampling networks and adjusting for location, the distance between the sampling points, and moss species. Data from the 2005/2006 and 2015/2016 moss surveys were chosen as instrumental neutron activation analysis was employed in both to determine the content of 34 elements (Al, As, Ba, Br, Са, Ce, Cl, Со, Cr, Cs, Fe, Hf, I, K, La, Mn, Na, Nd, Ni, Rb, Sb, Sc, Se, Sr, Ta, Tb, Th, Ti, Tm, U, V, W, Yb, Zn). In addition, Cd, Cu, and Pb were determined using complementary analytical methods: inductively coupled plasma atomic emission spectroscopy in 2015/2016 and atomic absorption spectroscopy in 2005/2006. For the subset of 57 routinely sampled locations in Bulgaria, hierarchical clustering on principal components and multiple factor analysis (MFA) were applied to assess the spatial trends in the 10 years elapsed between the surveys, as well as to characterise the origin of the determined elements. Elevation and distance between the sampling points were used as additional variables in the multiple factor analysis plane to ascertain their effect on the overall variance in the datasets. Distribution maps were constructed to illustrate the deposition patterns for the pollutant Pb. The results were consistent with decreased industrial output in the country, increased coal combustion and transport pollution, and construction of roads.
Keywords: Surveys and Questionnaires; Metals, Heavy; Biomonitoring; Metals; Environmental Monitoring; stopové prvky; Air Pollutants; Multiple factor analysis; Atmospheric deposition; průzkumy a dotazníky; látky znečišťující vzduch; monitorování životního prostředí; Bulgaria; Moss; Pollution; těžké kovy; Bryophyta; Trace Elements; GIS; Bulharsko